William Herbert Bixby papers - Bixby, William Herbert, 1849-1928.
Sketches and tracings (1882) of British turrets. Also lectures on sea coast fortifications, delivered at the U.S. Naval War College, 1886.
Engineer and army officer.
Collection material in English.
Keywords: Naval War College (U.S.); Fortification; Army officers; Engineers